Analysis of Comparison of Patient Preference for Two Insulin Injection Pen Devices in Relation to Patient Dexterity Skills - Antinori-Lent, Kellie J. (Diabetes Technology Society, 2012)
Insulin therapy is the cornerstone of medical treatment for many patients with diabetes. Self-administration of this life-saving medication is no longer limited to the traditional vial and syringe. Instead, more and more patients worldwide are using prefilled insulin pen devices. Ease of use, convenience, confidence in dosing accuracy, and improved quality of life are just a few of their advantages. As with any medical technology, safe and proper use is vital. Many studies have examined pen device preference and usability. Until now, no study has included patients with both visual and dexterity impairments. To ensure safe and simple self-administration of insulin for all patients, it is time for the special needs of patients with diabetes to be considered not only during product development, but during postmarketing studies as well.